PENGARUH BUDAYA BIROKRASI “ewuh-pakewuh” TERHADAP EFEKTIVITAS SISTEM PENGENDALIAN INTERN - Harry Indradjit Soeharjono (Jurnal Ilmu Administrasi: Media Pengembangan Ilmu dan Praktek Administrasi, 2019)
Within bureaucratic environment in Indonesia, “ewuh-pakewuh”- a manner steming from Javanese culture with themeaning 'to respect superiors or seniors more than necessary', still sticks to the bureaucrats in a certain situation, especially internal auditors when facing their superiors or top managers.The bureaucratic culture “ewuh-pakewuh” basically could make superiors or top managers out of control of their subordinates or internal auditors because they are reluctant to provide information or inputs needed by their superiors or top managers. Early warning system in this context obviously comes to a failure. On the contrary, the absence or weak control from subordinates or internal auditors results in the way the superiors or top management feel absolutely confident that their instructions should be complied whether it is going right or not, which refers to “the king can do no wrong”. In such situation, internal control system as a part of bureaucratic system to safeguard good governance within goverment institutions tends to be ineffective In fact, internal control system could not prevent fraud being done by some bureaucrats which ultimately come to corruption crime.